Evaluation of biomechanical properties and biocompatibility: are partially absorbable cords eligible for anterior cruciate ligament reconstruction? - Xu, Fei; Li, Yanlin; Yu, Yang; Wang, Guoliang; Cai, Guofeng (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Independent augmentation technology based on reinforcing devices has been reported to significantly reduce the elongation behavior of graft and improve knee stability after anterior cruciate ligament reconstruction(ACLR). Using biodegradable devices could reduce the risk of severe foreign body inflammatory reactions due to material particle accumulation. Given the limitations of the mechanical properties of biodegradable materials, partially biodegradable composite devices may offer a compromise strategy. Methods: In this study, three types of partially absorbable core-sheath sutures were braided with unabsorbable ultra-high molecular weight polyethylene (UHMWPE) yarn and absorbable polydioxanone (PDO) monofilament bundle based on the planned material configuration. Then , each single suture was further crocheted into a chain stitch cord. Three PDO/UHMWPE cords were low-absorbable cord (LA-C), medium-absorbable cord (MA-C), and high-absorbable cord (HA-C), respectively, according to the ascending proportion of PDO, and unabsorbable cord (UA-C) served as the control . The availability of these partially absorbable cords was verified by in vitro biomechanical testing, in vitro material degradation testing, and in vitro cell experiments. Results: As the proportion of PDO increased, the stiffnesses of the cords gradually decreased within 47-151 N/mm(UA-C＞LA-C＞MA-C＞HA-C), and the failure load exceeded 800 N except for MA-C (670.3±39.2 N). Reinforcement of an 8 mm graft by cords decreased dynamic elongation by 24-76%, positively related to dynamic stiffness, and increased failure load by 44-105%, during which LA-C showed maximum enhancement. During the degradation period of 16 weeks, the dynamic stiffness and dynamic elongation of MA-C and HA-C showed a significant upward trend due to gradual PDO destruction in the sheath during dynamic stretching, while UA-C and LA-C remained relatively stable, and only the failure load of the latter decreased slightly. Human ligament-derived fibroblasts showed good proliferation and vitality on each cord over two weeks and aligned themselves in the direction of the fibers, especially the UHMWPE portion. Conclusions: Overall, this study supports the potential of partially degradable UHMWPE/PDO cords, particularly LA-C, for graft protection. Still, the higher biodegradable material configuration that results in lower stiffness may impair this effect and lead to mechanical instability during degradation.